Time interval-based indication for liver resection of metastasis from pancreatic cancer - Yusuke Mitsuka; Shintaro Yamazaki; Nao Yoshida; Masahiro Yan; Tokio Higaki; Tadatoshi Takayama (World Journal of Surgical Oncology, 2020)
Abstract Background Surgical indications for liver metastases from pancreatic ductal adenocarcinoma (PDAC) are lacking because outcomes are usually poor. However, liver resection and the recent progress in perioperative chemotherapy have been observed to improve survival. Methods We performed liver resection for liver metastases from PDAC only under the following criteria: (1) liver-only metastasis, (2) up to three tumors, and (3) no increase in the number of metastases during the 3-month observation period. No limitations were placed on the location or size of liver metastasis. In this study, we aimed to validate our surgical criteria and analyze factors affecting survival in patients with PDAC. Results Seventy-nine patients underwent curative resection for PDAC between 2005 and 2015. Seventy-one patients experienced recurrence, with liver-only recurrence in 17 patients. Among these, nine patients underwent liver resection and eight did not. The median survival time was significantly better for patients who underwent liver resection (55 months) than for those with other recurrences (17.5 months, p = 0.016). The median survival after liver recurrence was significantly better in the liver resection group (31 months) than in the non-liver resection group (7 months, p = 0.0008). The median disease-free interval (DFI) after pancreatectomy was significantly longer in the liver resection group (21 months; range, 3–44 months) than in the non-liver resection group (3 months; range, 2–7 months; p = 0.02). Conclusion Good indications for liver metastases from PDAC include solitary metachronous tumors and longer DFIs.